Theoretical and X-ray studies on the cyclisation of 1-phenyl-5-(3-aryltriaz-1-en-1-yl)-1H-pyrazole-4-carbonitriles and 2-amino-3-(3-aryltriaz-1-en-1-yl)maleonitriles: A comparison study - Amal Al-Azmi; Firas F. Awwadi (Kuwait Journal of Science)
The present work investigates attempts to cyclise 1-phenyl-5-(3-aryltriaz-1-en-1-yl)-1H-pyrazole-4-carbonitriles to the desired pyrazolo[3,4-d][1,2,3]triazinimine derivatives. The cyclisations were unfruitful, and a density functional theory study was performed. This revealed the 1-phenyl-5-(3-aryltriaz-1-en-1-yl)-1H-pyrazole-4-carbonitriles are more stable than the targeted pyrazolo[3,4-d][1,2,3]triazinimine derivatives, indicating that their cyclisation is thermodynamically disfavoured. The effect of isomerisation of the methoxy-phenyl group in the self-assembly of 8c and 8d in the crystalline lattice was investigated.